The mediation role of RKA-SKPD review on the effect of effectiveness of government internal supervisory apparatus (APIP) and competence of regional financial management officials on budgetary planning - Maharani, Hasna; Yazid , Helmi; Yulianto, Agus Sholikan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze The Mediation Role of RKA-SKPD Review On The Effect of Effectiveness of Government Internal Supervisory Apparatus (APIP) and Competence of Regional Financial Management Officials on Budgetary Planning. The population in this study were 116 Government Internal Supervisory Apparatus (APIP) who worked in Regional Government Organizations (OPD) Serang Regency. The data used is secondary data. The data analysis technique used is quantitative. Structural Equation Modeling is used as an analysis with the help of Smart PLS software version 3.3.3. The results in this study indicate that The effectiveness of APIP and Competency of PPKD have a significant positive effect on Budgeting Planning and RKA-SKPD Review on APIP in Regional Government Organizations (OPD) Serang Regency. Budgeting Planning has a significant positive effect on the RKA-SKPD Review on APIP in the Regional Government Organization (OPD) of Serang Regency. The RKA-SKPD review can mediate the effect of APIP Effectiveness and PPKD Competence on Budgeting Planning on APIP in Local Government Organizations (OPD) Serang Regency.